In Their Own Language : Education for All - Bender, Penelope; Dutcher, Nadine; Klaus, David; Shore, Jane; Tesar, Charlie (World Bank, Washington, DC, 2012)
Fifty percent of the world's out-of-school children live in communities where the language of schooling is rarely, if ever, used at home. This paper discusses the benefits of use of first language instruction. The results of benefits from first language instruction discussed are: increased access and equity; improved learning outcomes; reduced repetition and dropout rates; socio-cultural benefits and lower overall costs. The paper outlines why many countries have been reluctant to deliver basic education in local languages. It also gives lessons learned on: policy formulation around language of instruction issues; bilingual programs; and management of the policy environment of language reforms.